Soviet mass-housing in vilnius: exploring the consequences of the 1955 housing reform and the rebellion against architectural homogenisation - Rimkutė, Kristina (The University of Edinburgh, 2014)
This paper contributes to the growing body of research in the field of Soviet mass-housing which started revealing the inherent complexities attached to the label of ‘Socialist Modernism’. In particular, this dissertation focuses on prefabricated housing in the former Soviet Lithuania, and analyses how the local building apparatus worked while also considering the role of the architect in this system. The historic research here relies heavily on articles published in the official architectural journal of Soviet Lithuania – Statyba ir Architektūra. Most extracts from this publication are presented in this dissertation for the first time in English translation. They serve as valuable insight into the contemporary politics of housing, as they help to reveal numerous contradictions in what was stated in propaganda literature and the actual reality of mass housing. As case-study districts for stylistic analysis, three residential areas in Vilnius are examined – Lazdynai, Karoliniškės, and Šeškinė. What seems to be clear from this comparative analysis is that Lithuanian architects were greatly involved in the process of designing mass-housing, and the appearance of the Vilnius’ residential districts evolved as a response to local criticism. As with many other former Soviet countries, visual monotony was fuelling people’s concerns in Lithuania, and so the local architects deployed to the best of their abilities all of the available design tools in order to give a distinctive look to each district. Inspired by experience-exchange trips to neighbouring Scandinavian countries, the Lithuanian architects approached the call for mass-housing with uniquely progressive and somewhat Westernised underlying ideologies. All of these aspects contributed to creating a distinctive look to residential districts in Vilnius.
Keywords: Architectural Conservation; Socialist Modernism; Mass Housing; Prefabricated construction